Inequalities in the UK 2017
DOI: 10.1108/978-1-78714-479-820171004
|View full text |Cite
|
Sign up to set email alerts
|

What the Minimum Income Standard Tells us About Living Standards in the United Kingdom

Abstract: The Minimum Income Standard (MIS) research gives an insight into living standards in the UK, and provides a way of tracking the (in)adequacy of incomes over time. As such it offers useful context for discussions of inequality. At the core of the research are deliberative groups held with members of the public who identify and discuss the goods and services that are considered necessary for a living standard that provides a socially acceptable minimum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…This research has found that watching television with others and watching the same program as others are each associated with feelings of belonging and the need for company (Cohen and Lancaster 2014 ), which were implied in the conversations held in groups in Mexico. Similarly, participants in MIS research in other countries have agreed that having a television helps to fulfill the need for information, connectedness, and social interaction (see Collins et al 2012 for Ireland and Davis et al 2016 for the UK).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This research has found that watching television with others and watching the same program as others are each associated with feelings of belonging and the need for company (Cohen and Lancaster 2014 ), which were implied in the conversations held in groups in Mexico. Similarly, participants in MIS research in other countries have agreed that having a television helps to fulfill the need for information, connectedness, and social interaction (see Collins et al 2012 for Ireland and Davis et al 2016 for the UK).…”
Section: Resultsmentioning
confidence: 99%
“…In the United Kingdom, baskets of goods and services included in the MIS project are updated every 2 years (Davis et al 2016 ). In the UK, for example, households above pension age introduced a home computer and internet access into their budgets in 2014, arguing that being able to access online facilities was necessary for personal development and in order to be part of society (Davis et al 2014 ). Currently, the non-food basket in Mexico is updated only with inflation (CONEVAL 2012 ) and expanding the pilot of the MIS project could provide the opportunity to change or adjust the contents both in terms of quantity and quality as well as price.…”
Section: How the Mis Approach Sits Within The Mexican Context Of Measmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides the income required by different households based on the costs of items and services members of the public believe are needed to reach a minimum acceptable standard of living which enables household members to participate fully in society. In 2016, this figure was estimated at £267.39 per week for a pensioner couple or £186.77 for a single pensioner, after housing costs (Davis et al 2016). As such, if pensioners are claiming Pension Credit, arguably they should have an income in line with the minimum income required for an appropriate standard of living (Age UK 2014).…”
Section: Older People Low Income and Povertymentioning
confidence: 99%